Pengembangan Aplikasi Informasi Calon Anggota Legislatif Pada Pemilihan Umum (PEMILU) 2019 Dengan Menerapkan Konsep Gamifikasi Dan Pendekatan Hybrid - Doni Putra Purbawa; Herman Tolle; Lutfi Fanani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The general election of legislative candidates in Indonesia is the biggest election and being a spotlight of the world. There were 14,556 reports related to the legislative elections and 3,318 or 23 percent regarding election violations, such as gratuities, bribery, vote inflating, political money, administrative violation, and deceptive news. Even in campaigning it still contain political money and invalid information. The campaign media using banner, and a piece of paper as well as still unable to get to know the legislative candidates more closely. Nowadays, the gamification method is considered very effective in attracting people to be more interactive and consumptive in using the application. Some elements in gamification method which are points, bagdes, levels and ranking have also been implemented in various domains such as training, education, health and other. The development model with a hybrid approach is also currently very popular because it saves energy, time, cost, and can be implemented in two different platforms which are Android and iOS. To overcome these problems, researcher developed an information legislative candidates application by applying the concept of gamification and hybrid approach using the Ionic Framework. From the research result, founded an usability value of 80.5% which indicates that the application can be well received by the user, then the compatibility value of 100% in 3 different platform experiment, which means the hybrid approach runs well, and based on the average of the user's answer from the question of a positive SUS questionnaire of 92.8% and a negative SUS questionnaire of 44%.